Perceived and experienced stigma among people living with HIV: Examining the role of prior stigmatization on reasons for and against future disclosures. Issue 2 (2nd April 2016) - Catona, Danielle; Greene, Kathryn; Magsamen-Conrad, Kate; Carpenter, Amanda
ABSTRACT: HIV remains a significant health concern entering the fourth decade of the epidemic [Centers for Disease Control and Prevention. 2014. HIV basics . Retrieved fromhttp://www.cdc.gov/hiv/basics/index.html ], and people living with HIV continue to grapple with stigma. This study uses Leary and Schreindorfer's [1998 . The stigmatization of HIV and AIDS: Rubbing salt in the wound. In V. J. Derlega & A. P. Barbee (Eds.), HIV and social interaction (pp.12 –29 ). Thousand Oaks, CA: Sage] conceptualization of stigma to explore prior stigmatization on reasons for and against future disclosures. We interviewed HIV+ individuals ( N = 59) and used a combination of deductive and inductive coding to analyze participants' responses. Deductive codes consisted of four stigma characteristics (pose a threat to others' health and safety, deviate from group standards, create negative emotional reactions in others, and failure to contribute), experiences of feeling stigmatized due to HIV status (yes or no), and the degree to which HIV stigma was a concern (major, minor, or no concern). Inductive coding identified examples of perceived and experienced stigma and stigma concerns on future disclosure decision-making. Practical implications discuss individual, institutional, and societal stigma-reduction interventions and programs.